The Relationship of Community Knowledge and Attitude Towards Earthquake Disaster Management Efforts - Haryawan, I Gusti Agung; Prihastini, Komang Angga; Kusuma, Made Adhyatma Prawira Natha (Indonesian Journal of Global Health Research, 2024)
Indonesia is highly vulnerable to natural disasters, with regions across the country frequently affected by events such as earthquakes, tsunamis, and volcanic eruptions. Key factors contributing to high casualty rates and significant losses during disasters include limited understanding of hazard characteristics, attitudes or behaviors that degrade natural resources, lack of early warning information, and overall unpreparedness. Ban Village, located in Kubu District, Karangasem Regency, lies in a disaster-prone zone close to Mount Agung and Mount Abang. Following a recent earthquake, Cegi Hamlet, in particular, suffered extensive damage, with many homes destroyed and residents lacking adequate disaster response knowledge and skills. This study aimed to assess the knowledge and attitudes of Cegi Hamlet residents toward earthquake disaster preparedness. The research employed a cross-sectional study design with a target population of Cegi Hamlet residents who met specified inclusion and exclusion criteria. A sample of 80 respondents was selected using purposive sampling. Data were collected through a structured questionnaire measuring levels of knowledge, attitudes, and responses to earthquake disasters. Data analysis involved the Kolmogorov-Smirnov test for distribution analysis, which indicated a non-normal distribution, followed by Spearman's Rank correlation to examine the relationship between knowledge and attitudes. The results indicated a significant positive relationship between knowledge and attitudes toward earthquake disaster response efforts (p = 0.000, p < 0.05). In conclusion, there is a significant correlation between community knowledge and attitudes in Cegi Hamlet, Ban Village, Karangasem Regency, suggesting that enhancing knowledge could positively influence disaster preparedness and response behaviors.